Unraveling the role of peroxisome dynamics in cancer development - Valença, Isabel Cristina Pinto (2021)
Peroxisomes are multifunctional and highly dynamic intracellular organelles, essential for human health and development.Over the years, several reports showed a direct association between peroxisomes and different types of cancer. Prostate cancer (PCa) displays an exclusive metabolic profile. In contrast with most cancer cells, that use glucose as main energy source, PCa in early stages consumes low rates of glucose and the lipids are the main energy source, being β-oxidation pointed as the dominant bioenergetic pathway in PCa cells. The monocarboxylate transporter 2 (MCT2), a membrane transporter typically associated with glucose metabolism, was shown to be overexpressed and mislocalized in PCa tissues. The aim of this work was to understand the role of MCT2 in PCa. Our results demonstrate that MCT2 localizes at the peroxisomal membranes in PCa cells and suggest a possible role for peroxisome-related mechanisms in prostate malignant transformation, likely associated with increased β-oxidation rates. We have also shown that PCa takes advantage of the peroxisomal membrane transport machinery to target MCT2 to peroxisomes. Furthermore, the important role of this organelle in the early stages of PCa is supported by the observations of increased import of peroxisomal matrix and membrane proteins to potentiate their metabolic capacity, as well as the increased transport of branched fatty acids and their degradation for energy production. Our data clearly show that MCT2 is directly associated with changes in peroxisomal morphology and number in PCa. Furthermore, our results showed that MCT2 promotes PCa migration and proliferation and, remarkably, that MCT2’s peroxisomal localization is essential for PCa proliferation. Moreover, our results indicate that MCT2 is localized at peroxisomes in liver and cervix cancer, suggesting a putative role in these cancers. Altogether, our results highlight the importance of the interplay between peroxisomes and MCT2 in PCa, exposing a range of possible targets for its therapy.